50S Ribosomal Proteins Family is the Main Target of Cinnamon Extract: a Network Analysis - Mostafa Rezaei Tavirani; Mahmood Khodadoost*; Babak Arjmand; Mohamadreza Razzaghi; Alireza Ahmadzadeh (Iranian Society of Pharmacognosy, 2021)
Background and objectives: It is reported that cinnamonconsumption is corelated with improving several diseases and advanced methods are applied to detect the molecular mechanism of this effect. The aim of this study was introducing the main protein targets of cinnamon extract. Methods: Among the 100 regulated significant differentially expressed proteins, the recognized individuals by STRING database plus 100 added first neighbors were included in a network and the central nodes of the network were determined and analyzed. Results: The queried and added proteins were included in a scale free network. Seven hub nodes as central proteins were determined as critical target proteins. Five hub proteins were members of 50S ribosomal proteins family and others weretsf and dnaK. The last two hubs were related to protein synthesis and protein folding processes, respectively. Conclusion: 50S ribosomal proteins family and protein synthesis were identified as the main target of cinnamon and the core affected process, respectively.